Effects of Five-Finger Relaxation Technique on Depression in Type 2 Diabetes Mellitus Patients - Dewi, Rosliana; Agustina, Fanny Dwi; Budhiana, Johan; Fatmala, Syiva Dwi (Jurnal Keperawatan Soedirman, 2021)
Diabetes mellitus (DM) can cause physical and psychological changes for sufferers. Psychological changes include changes in self-concept and depression. Psychological changes can be treated with nonpharmacological therapies, one of which is five-finger relaxation technique. The research aimed to reveal the effect of five-finger relaxation technique on depression experienced by type 2 DM patients. The five-finger relaxation technique is one of the generalist relaxation techniques by recalling pleasant experiences. This research is a quasi-experiment. Samples of this research were 34 respondents whom were selected using purposive sampling. The intervention was carried out once a day for 3 consecutive days. In order to measure depression, a valid and reliable questionnaire of Indonesian version of the Beck Depression Inventory (BDI) was employed. Data were analyzed using the Wilcoxon Test and the Mann-Whitney Test. The results showed the was a decrease in depression in the control group (p-value of 0.008) and the intervention group (p-value of 0.000) and there were differences in depression in the control group and the intervention group (p-value of 0.000). It can be concluded that there is an effect of five-finger relaxation technique on depression in type 2 DM patients.